Use of Radiotherapy in Advanced Breast Cancer: The Role of a Nurse - Cloconi, Constantina; Georgiou, Christina; Zamba, Nicole; Zamboglou, Constantinos; Ferentinos, Konstantinos (My University, 2024)
Systemic therapy is the mainstay in advanced breast cancer (ABC), but innovations in radiation oncology have given radiotherapy a crucial role in the treatment of both intracranial and extracranial ABC. Breast cancer specialists include, in addition to medical and clinical oncologists, breast cancer nurses with unique theoretical knowledge and significant clinical experience. This review aims to discuss the function of radiotherapy in ABC and to highlight the role and importance of specialized nursing care for ABC patients receiving radiotherapy.
Keywords: Cancer; Metastasis; Nurse; Radiotherapy; Unmet needs; International performance